Subscribing to gendertrash: The Radical Subcultural Transmissions of Toronto’s Original “TransZine” - Cunningham, Sidney (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2019)
This article situates the Canadian zine series gendertrash between the international political context of early 1990s trans periodicals and its material roots in Toronto’s Church-Wellesley village, while also providing a brief discussion of how its form and distribution relate to contemporary scholarship on the zine as genre. Published cross-promotional materials in a number of influential trans periodicals from Canada and the United States, as well as archived correspondence, demonstrate the ‘zine’s involvement in broader networks of solidarity and resource-sharing – against which the radical politics of this early “gender queer” publication become all the more apparent. The ArQuives’ 2017 gendertrash digital collection promises an expanded sense of trans cultural inheritance yet raises ethical questions around privacy and archival categorizations of identity. This article concludes, building on earlier critiques of similar digitization projects, by positing an affect-based analogy between the role of gendertrash’s subscription/distribution model and that of this recent digital collection.